Ochotnicze straże pożarne zasługują na odrębną ustawę - Ręcławowicz, Stanisław (Wydawnictwo Uniwersytetu Wrocławskiego. Wydawnictwo "Szermierz" sp. z o.o., 2023)
Establish the State Fire Service Act and the Voluntary Fire Brigades Act, although made in long time distance, was proceeding in similar atmosphere. The Voluntary Fire Brigades Act regulate the situation of social organisations, which have a status of association. Voluntary Fire Brigades, as well as State Fire Service, are responsible for rescue activity, but also their activity is focused on local communities.
Keywords: voluntary fire brigades; the Voluntary Fire Brigades Act (project); fire protection; activity of behalf of local communities